Breathlessness despite optimal pathophysiological treatment: on the relevance of being chronic. Issue 3 (28th September 2017) - Calverley, Peter M.A.
Morélot-Panzini and colleagues response to the paper by Johnson et al. [1] is an important contribution to the debate about the chronic breathlessness syndrome, which I called for in my editorial [2] and to which others have already contributed [3, 4]. English is a greedy language using words that mean the same in their original tongue to denote slight differences in meaning in English. In this case, dyspnoea is the technical term for breathlessness. In 40 years of clinical practice I never met a patient who complained of dyspnoea but saw many who were greatly affected by what they called breathlessness. This distinction between the symptom and its impact are at the heart of the discussions around the chronic breathlessness syndrome. I strongly support the need to provide more holistic care that looks at the consequences of breathlessness as well as their causes. However, important secondary effects on mood, behaviour and lifestyle occur in many chronic conditions not fully controlled by medical-management strategies. Should we refer to chronic arthritis syndrome or chronic cluster headache syndrome or any of the numerous other examples which readily suggest themselves? Whether or not we use the word syndrome these patients need better care than they currently receive. Chronic breathlessness is an under-recognised problem irrespective of the terminology used to describe it http://ow.ly/kKQs30es6A8